Infrared detector / Md Rahizan Md Berhannudin - Md Berhannudin, Md Rahizan (2002)
The infrared detector (Latch switch) is function as a TV Remote. This Project well be function when infrared receiver detected infrared Signal. When the signals are detected, switch in receiver circuit will be on. The infrared detector (Latch switch) needs two circuits. First circuit is a Infrared Transmitter and second circuit is an infrared receiver and latch switch. Infrared Transmitter will function when we push on the PTT switch, infrared Beam generate from LI and L2 (Infrared diode). Infrared receiver will function when the sensor detected infrared beam and LI is on. The cost of this project is amount RM 40 to RM 50.